Significant Improvement of the Recombinant Borrelia-Specific Immunoglobulin G Immunoblot Test by Addition of VlsE and a DbpA Homologue Derived from Borrelia garinii for Diagnosis of Early Neuroborreliosis - Schulte-Spechtel, Ulrike (American Society for Microbiology, 2003)
We investigated whether the recombinant Borrelia Western blot test previously described (B. Wilske, C. Habermann, V. Fingerle, B. Hillenbrand, S. Jauris-Heipke, G. Lehnert, I. Pradel, D. Rössler, and U. Schulte-Spechtel, Med. Microbiol. Immunol. 188:139-144, 1999) can be improved by the addition of VlsE and additional DbpA and OspC homologues. By using a panel of sera from 36 neuroborreliosis patients and 67 control patients, the diagnostic sensitivity of the recombinant immunoblot test was significantly increased (86.1% versus 52.7%) without loss of specificity and was higher (86.1% versus 63.8%) than that of the conventional whole-cell lysate immunoblot test (U. Hauser, G. Lehnert, R. Lobentanzer, and B. Wilske, J. Clin. Microbiol. 35:1433-1444, 1997). Improvement was mainly due to the presence of VlsE and DbpA.